(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
The Egyptian Fertilizers Company (EFC) is situated in the Ain Sukhna region within the northwestern sector of the Gulf of Suez in Egypt. Twelve groundwater samples were procured from wells within the investigated area, and the presence of nitrogenous ions such as nitrate, nitrite, and ammonia was rigorously examined. To assess the quality of the water, ratios are utilized, emphasizing nitrate concentration, and the findings are juxtaposed with the guidelines established by the World Health Organization (WHO). The statistical methodologies endorsed by the United States Environmental Protection Agency (US-EPA) are employed to evaluate the health risks posed to the local populace. The findings indicate that the nitrate concentrations exceeded WHO thresholds in seven samples, nitrite levels exceeded in two samples, and ammonia contents exceeded in all samples, rendering the water unfit for human consumption. Elevated concentrations of NO3 in the water samples were associated with anthropogenic activities, including the amalgamation of mixed wastewater and seawater intrusion. Nitrate levels surpassed the WHO (50 ppm) and US-EPA (10 ppm) standards, thereby presenting a non-carcinogenic risk from oral exposure, particularly for children, as hazard values exceeded the safety threshold (1). Conversely, dermal exposure did not present any significant risk. Nitrate can be converted to nitrite and N-nitroso derivatives via bacterial nitrification, which may induce carcinogenic effects within the digestive, urinary and excretory systems. Consequently, the remediation of the contaminated wells is imperative to safeguard the health of the local community.